Additional Description to Two Newly Recorded Plants from Karnataka - Hegde, R.Gurumurthi; Prakash, D.; Hebbar, S. S.; Bhat, K. G.; Hegde, R. Ganesh (Indian Forester, 2010)
During the floristic survey of Uttara Kannada and Udupi districts of Karnataka, authors came across two herbaceous taxa viz. Ceraeioearpum bennetti (Miq.) Cogn. (Cucurbitaceae) and Gymnostachyum polyanthum Wt. (Acanthaceae). Additional informations noticed in these plants form an amendment in the description of these plants.